If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 4 = 5x + -1 Reorder the terms: 4 + 7x = 5x + -1 Reorder the terms: 4 + 7x = -1 + 5x Solving 4 + 7x = -1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 4 + 7x + -5x = -1 + 5x + -5x Combine like terms: 7x + -5x = 2x 4 + 2x = -1 + 5x + -5x Combine like terms: 5x + -5x = 0 4 + 2x = -1 + 0 4 + 2x = -1 Add '-4' to each side of the equation. 4 + -4 + 2x = -1 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = -1 + -4 2x = -1 + -4 Combine like terms: -1 + -4 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5
| 2=f/2 | | -182=-6(7-6n)-n | | 4z^2-16+12=0 | | 7x+3/2-9x-8/4=6 | | -22-x=3w-w+4w | | 4/5x+4/3+2x | | 1/5x-y=76 | | -7p-(-7+5p)=-4(3p-7) | | 5(1+7)-5=175 | | x+4/15=-1 | | (7x^2-7x+8)+(9x^3-5x)= | | 3(x+3)+12=6x+3 | | 5(2a-4b)= | | -4(n+6)=12 | | 19=4+3v | | -x-4+3x=x-3+1 | | 7(x+5)=13 | | 4-6a+4a=-115(7-2a) | | 5x+47= | | 11/6x6/35 | | 4(2a-6)+8b= | | (3x+39/8)=0 | | 7k-2(3k+1)= | | 5x-1+x=15 | | 11=((7w-9)/2)+((8w+1)/5) | | y/8+4=6 | | 9(2/3+x)=24 | | 4x+9=8-6x | | 18-.10x=34 | | 3[7r-7]=-6+6r | | 7n-5n=9(n+7)-7(n+10) | | -5x1/4x4 |